Comparison of the Interest in Entrepreneurship of Students and Vocational Students in Padang - Rusmardi, Rusmardi; Desi, Yulfi (International Journal Labs, 2023)
Labour is a huge potential in the development of work and is closely related to the skill level, number and population growth, the state of the job market, and the mental attitude or college diploma in either general or vocational. The research would like to compare the interest in entrepreneurship of students and vocational students in Padang. The research hypothesis that will be answered through this research is “there is significant lnear, relationship of parenting methods, information, and attitude, together with the information of entrepreneurial interest. Data collected parenting methods, information, attitude towards the information of interested in entrepreneurship. Data were analysed by logistic regression and for dummy variables with scores above the median = 1 and score below the median = 0. The was a significant linear relationship between parenting methods, information, and attitude together the same towards the information of the entrepreneurial interest students. The result of students of Padang State Polytechnic showed that significant linear regression of entrepreneur information to entrepreneur intention and significant linear correlation among variables that are information, model of parents guidance, and attitude of entrepreneur cooperation with entrepreneur intention.